2012
DOI: 10.1088/1748-9326/7/4/045706
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 spring drought reduced primary productivity in southwestern China

Abstract: Many parts of the world experience frequent and severe droughts. Summer drought can significantly reduce primary productivity and carbon sequestration capacity. The impacts of spring droughts, however, have received much less attention. A severe and sustained spring drought occurred in southwestern China in 2010. Here we examine the influence of this spring drought on the primary productivity of terrestrial ecosystems using data on climate, vegetation greenness and productivity. We first assess the spatial ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(122 citation statements)
references
References 47 publications
8
113
1
Order By: Relevance
“…The rainfall percentage anomaly in some regions was 60.4% less than in previous years [5] and rainfall in February decreased by 49.5% compared to 2000-2009 average precipitation [38]. The continuous drought in the autumn, winter, and spring in some regions of Yunnan and Guizhou provinces was the most serious since 1880, and the extent and severity of drought broke historical records [5].…”
Section: Figurementioning
confidence: 84%
See 1 more Smart Citation
“…The rainfall percentage anomaly in some regions was 60.4% less than in previous years [5] and rainfall in February decreased by 49.5% compared to 2000-2009 average precipitation [38]. The continuous drought in the autumn, winter, and spring in some regions of Yunnan and Guizhou provinces was the most serious since 1880, and the extent and severity of drought broke historical records [5].…”
Section: Figurementioning
confidence: 84%
“…From 2009 to 2010, Southwestern China experienced a serious drought that affected extensive regions from Yunnan, Guangxi to Sichuan, Guizhou and Chongqing [5,38]. Figure 1 shows the unchanged land cover of Southwestern China, and the red square defines the study area.…”
Section: Study Areamentioning
confidence: 99%
“…The abrupt decrease in precipitation favored the intensification, such as severity, duration and extent, of the severe drought event for this area. Fortunately, the precipitation was larger for 2014 and 2015 (Figure 4a), which could mitigate the drought severity of 2009-2011 [12,[51][52][53].…”
Section: Impacts Of Change In Aridity Index On Droughtmentioning
confidence: 99%
“…Because the affected area is a major grain-producing region that includes a large population and complex land cover, this severe drought event not only significantly affected the daily lives of millions of people but also impacted the structure, function, and services of terrestrial ecosystems (Qiu, 2010). Zhang et al (2012) recently reported on a severe decline in ecosystem productivity in southwestern China in the springtime of 2010. Nearly 63% of the region exhibited a decline in vegetation productivity (e.g., a reduction of 4% and 5% in regional annual GPP and NPP in 2010, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…To reconcile these inconsistencies, this study examined the quality of data used in the recent study by Zhang et al (2012). The main objectives of this study aimed to address the following questions: (1) Was the MODIS GPP product affected by atmospheric contamination during the 2010 springtime drought period?…”
Section: Introductionmentioning
confidence: 99%